1995
DOI: 10.1007/bf00309386
|View full text |Cite
|
Sign up to set email alerts
|

Serum-soluble interleukin-2 receptor levels before and after surgical treatment for graves' disease

Abstract: Serum-soluble interleukin-2 receptor (ssIL-2R) is released from its specific affinity membrane receptor on activated T lymphocytes and is detected as a form of the alpha-chain of IL-2R in the peripheral blood. We measured the ssIL-2R levels by enzyme-linked immunosorbent assay in 29 healthy subjects and 39 patients with Graves' disease who were given antithyroid drugs to prepare them for surgical treatment. The preoperative ssIL-2R levels in Graves' patients were significantly higher than those in the healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…[24][25][26][27][28][29][30][31][32] T lymphocytes activated by IL-2 shed part of the a-chain as a serum-soluble form into the bloodstream. This fragment of the a-chain of IL-2R is generally called serumsoluble IL-2R (sIL-2R).…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32] T lymphocytes activated by IL-2 shed part of the a-chain as a serum-soluble form into the bloodstream. This fragment of the a-chain of IL-2R is generally called serumsoluble IL-2R (sIL-2R).…”
Section: Discussionmentioning
confidence: 99%
“…4 Therefore, the serum sIL-2R, thanks to its relatively long half-life (several hours) and the ease of detecting it in the serum, is popularly favored to measure the quantity of T lymphocytes activated by IL-2. Increased levels of serum sIL-2R have been found in patients not only with various malignant tumors, [5][6][7][8][9][10][11][12] but also with infectional diseases, 13,14 autoimmune diseases, [15][16][17] or organ transplantations. 18 Recent studies demonstrated that serum sIL-2R could be used to evaluate the disease stages of cancers and as an indictor of prognosis in patients bearing malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of serum soluble IL-2R can be recognized in the patients not only with malignancy but also with inflammatory diseases. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, there have been few reports on the changes in the serum sIL-2R concentrations in patients after surgical stress. Therefore, this study investigated the changes in the serum-soluble IL-2R levels and the relationship of such changes with other cytokines to clarify the status of cell-mediated immunity after surgical stress.…”
mentioning
confidence: 99%
“…T lymphocytes activated by IL-2 release a serum soluble form of IL-2R into the bloodstream. High levels of soluble IL-2R were observed in patients with various malignant diseases, autoimmune disorders, infections and many other inflammatory diseases [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 18, 19, 20, 21]. There are some reports regarding the levels of IL-2R in patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1). Increased levels of serum soluble IL-2R have been found in patients with diverse diseases including lymphoma [2], lung cancer [3], gastrointestinal cancer [4, 5, 6, 7, 8], breast cancer [9], autoimmune diseases [10, 11, 12], infections [13, 14]and organ allograft rejection [15], for example. We have already reported increased concentrations of serum soluble IL-2R in patients with gastric cancer [4].…”
Section: Introductionmentioning
confidence: 99%